Encapsulation Of black seed oil in alginate beads : formulation, characterization, and stability evaluation - Alkhatib, Hamzeh (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Taste of medicines has a high number of reports as an administration problem for paediatric medicines. Black seed oil (BSO) is known widely for its medical applications, but children are facing difficulties to take it orally because of its bitter taste. Alginate as a polymer is widely used to encapsulate medications for different purposes including taste masking. Thus, the objectives of this study were to characterize BSO in terms of thymoquinone (TQ) content as the major bioactive compound, to formulate and characterize the alginate beads containing BSO, to study the stability of the beads and to evaluate the taste masking efficacy in human. Stability-indicating HPLC method for TQ analysis in BSO was validated. For encapsulation of BSO in alginate beads, BSO was emulsified with 2% w/v alginate solution by the aid of Tween 80 as a stabilizer. The concentration of BSO and Tween 80 was selected as 15% v/v and 5% w/v respectively to obtain the most stable emulsion. The optimized emulsion was dropped wisely into 1% w/v calcium chloride bath to fabricate BSO-alginate beads. Electrospray technique was used to apply controlling on size of the produced beads. Influence of changing flow rate of BSO-alginate emulsion and applying various values of high voltage on each of encapsulation efficiency, shape and size of the beads were studied. It was found that BSO was completely encapsulated within alginate beads without any significant difference during changing both the flow rate and values of high voltage. All the fabricated beads were in spherical shape. Size of the beads decreased significantly as the value of the applied high voltage increased. On the other hands, changing the flow rate did not have influence on the beads size without applying high voltage. While the beads size decreased significantly as the flow rate increased during applying high voltage. Based on the factorial design analysis and to make producing of BSO-alginate beads is more practical, flow rate of BSO-alginate emulsion was selected at 0.8 mL/min. Moreover, the applied value of high voltage was selected at 4000 v to produce beads within average size of 1.1 mm. The in vitro release study showed that all amount of BSO was released at 110 min in simulated intestine medium. Attenuated total reflection-Fourier Transform infrared spectroscopy (ATR-FTIR) and differential scanning calorimetry (DSC) analysis showed that BSO was encapsulated in alginate beads without chemical or physical interactions with the excipients. Stability study was carried out under real time and accelerated conditions. TQ in encapsulated BSO was more stable than TQ in aqueous solution and in original BSO. Moreover, visual inspection and ATR-FTIR confirmed stability of BSO-alginate beads against oil leaking. Evaluation of BSO-alginate beads palatability was done based on an open-label, single-dose study in adults. Encapsulation of BSO in alginate beads significantly improved the oil palatability, making it more accepted to be administered. This study suggests that encapsulation of BSO in alginate beads can improve the oil palatability especially the taste without reducing TQ stability, making BSO more suitable as pediatric formulation.